Proposing an agricultural belt to protect a city's semi-rural characteristics: The example of Bartin, Turkey - Gormus, Sevgi; Cengiz, Serhat; Tagil, Sermin (Routledge Journals, Taylor & Francis Ltd, 2019)
Urban sprawl, a type of urban expansion, is perceived as a global problem due to changes in land conversions and landscape patterns. Farms, forests and shores have been converted into urban areas; this transformation affects energy flow, biochemical cycles and climatic conditions. To follow and evaluate the physical, social and ecological results of urban sprawl, we identified and measured temporal changes in land use and land cover. This is especially important for urban planning policies. In this study, temporal change is identified in the city of Bartin using remote sensing and landscape metrics. An analysis of land cover and land transformation was done with LANDSAT5 TM/ETM satellite images from 1985 and 2015. These images were used to identify agricultural areas as land that has most commonly undergone drastic changes. Bartin is a small semi-rural city that has undergone significant changes. Among the most important reasons for these changes were uncontrolled urban sprawl due to political and administrative decisions that lacked long-term planning and a comprehensive city plan. This study examined the risk factors for loss of semi-rural characteristics using the example of Bartin city. To protect semi-rural city characteristics and control urban sprawl, we propose an agricultural belt based on spatial suitability and an evaluation of landscape metrics.
Keywords: Urban Sprawl; Landscape Change; Agricultural Belt; Bartin; Turkey